2011
DOI: 10.1021/ac102489y
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive in Situ Label-Free DNA Detection Using a GaN Nanowire-Based Extended-Gate Field-Effect-Transistor Sensor

Abstract: In this study, we have successfully demonstrated that a GaN nanowire (GaNNW) based extended-gate field-effect-transistor (EGFET) biosensor is capable of specific DNA sequence identification under label-free in situ conditions. Our approach shows excellent integration of the wide bandgap semiconducting nature of GaN, surface-sensitivity of the NW-structure, and high transducing performance of the EGFET-design. The simple sensor-architecture, by direct assembly of as-synthesized GaNNWs with a commercial FET devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(66 citation statements)
references
References 28 publications
2
63
0
1
Order By: Relevance
“…Interesting works have described the use of EGFET as component of a biosensor to detect, for example, DNA 9,10 , CO 2 11 , O 2 …”
Section: Introductionmentioning
confidence: 99%
“…Interesting works have described the use of EGFET as component of a biosensor to detect, for example, DNA 9,10 , CO 2 11 , O 2 …”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of MEMS and NEMS-based sensors is broadly similar to those of existing electrochemical or optical techniques (Liu et al, 2012;Sassolas et al, 2008); and some groups have reported superior sensitivities Chen et al, 2011). However, with some exceptions, MEMS and NEMSbased oligonucleotide sensors are label-free which renders their sensing mechanisms far simpler than most electrochemical or optical techniques in terms of steps involved and reagents required.…”
Section: Introductionmentioning
confidence: 82%
“…However, other materials such as gold (Andreu et al, 2006;Fang and Kelley, 2009), gallium nitride (Chen et al, 2011), carbon nanotubes (Sorgenfrei et al, 2011;Star et al, 2006), graphene oxide (Stine et al, 2010) and indium oxide (Tang et al, 2005) have been used. It is also possible to exploit NWs for oligonucleotide sensing in ways other than the FET-based approach that has been described.…”
Section: Nanowiresmentioning
confidence: 99%
“…For example, Dai and coworkers developed carbon nanotube-based FET for detection of protein or protein-protein interaction in wide-ranging concentrations from 100 pM to 100 nM [13]. Chen et al presented a kind of GaN nanowires based extended-gate FET biosensor capable of specific and sensitive (10 -18 M) DNA sequence identification [27].…”
Section: Sinws-based Field-effect Transistormentioning
confidence: 99%